Evaluation of yield, quantitative and qualitative attributes of three amaranth species grown under organic medium enclosed Trough system - Mopai, Maeleletse Glas (My University, 2023)
Amaranth species are a highly popular group of vegetables rich in primary and secondary metabolites, with potential to significantly reduce food insecurity and malnutrition. Yet, their production levels in South Africa (SA) remains unknown and limited to small scale farming where water scarcity is also a problem. Although the production rate of Amaranth is unknown in RSA, the consumption Amaranth has increased over the last few years. The Organic Medium Enclosed Trough (OMET) system is a non-drainable growing technique. OMET system supports and promotes organic and sustainable farming. The aim of the study was to investigate the effects of the OMET system on growth and yield in three Amaranth species, including: A. caudatus, A. cruentus and Amaranthus Spp. Data collected for the growth attributes were seedling height, stem diameter, leaf length, root length and time of flowering; whereas for yield attributes, mass of the aerial parts was determined. The nutritional composition data was acquired from determination and quantification of carbohydrates, protein, minerals (Ca, Zn, P, Se, Mg, and Mn) and amino acids. The amount of water used on the OMET and non-OMET (control) was recorded until termination. T-test at 5% level of significance was used to analyse data using computer statistical software, Statistix 10.0. This study revealed that the OMET system had significant impact on the growth and yield of all the three species as shown by the improved and increased growth and yield attributes of the Amaranth. The OMET system increased the stem diameter, plant height and leaf length of A. caudatus by 2.8%, 10.5% and 2.6% respectively; A. cruentus by 25.2%, 21.6% and 11.2% respectively, by 32.4%, 41.2% and 39.6% respectively in Amaranthus Spp. The OMET system increased the root length of A. caudatus, A. cruentus and Amaranthus Spp. by 8, 50.1 and 94.5% respectively. Furthermore, the OMET system significantly increased the mass of aerial parts of A. caudatus, A. cruentus and Amaranthus Spp. by24.4, 12.6 and 91.9% respectively. The nutritional and phytochemical (targeted and untargeted) compositions of the three Amaranth species were quantified/determined and compared independently for each Amaranth species grown under OMET and control. The essential and nonessential amino acids were determined and quantified, and it has been shown that they are highly available in OMET grown A. cruentus. Furthermore, both A. cruentus grown under non-OMET and Amaranthus Spp. grown under OMET system showed to be the second potential sources of amino acids compared to other Amaranth species grown under distinct treatments. The levels of phenylalanine (2.54 mg/kg), leucine (2.21 mg/kg), valine (1.45 mg/kg), isoleucine (1.29 mg/kg) and threonine (1.15 mg/kg) were dominant in all three Amaranth species but highest in A. cruentus grown under OMET system The results of this study indicate that the OMET system has enhanced the concentration of carotenoids and chlorophyll, although this increase is not significant inin Amaranth species grown under both treatments (OMET and non-OMET). The highest caretonoid (59.56 mg/kg) and chlorophyll (48.08 mg/kg) were obtained in A. caudatus grown under non-OMET and OMET system respectively. The other targeted metabolites including phenolics, flavonols and tannins were measured highest concentrations in Amaranth species that were grown under non-OMET system compared the same species grown under OMET system. The total phenolics, flavonols and tannins were specifically dominant in A. cruentus (276.88 mg GAE/100 g DW), A. cruentus (448.56 mg CA/100 g DW) and A. caudatus (10.5 mg CA/100 g DW). The study also revealed that the OMET system utilised less water than the non-OMET system.In addition, OMET system improvedthe growth attributes such as stem diameter, plant height, leaf length, and fresh biomass and nutritional composition of the three Amaranth species. On the other hand, the OMET system decreased the accumulation of the secondary metabolites such as total phenolic acids, flavonols and tannins. But the non-OMET system (control) significantly increased the concentration of the above mentioned targeted metabolites in the three Amaranth species. The OMET system is a sustainable and organic growing technique that produces more yield relatively on a small area while utilizing less water, making it a brilliant strategy to conserve and utilise water sustainably and effectively. This can be important for smallholder farmers who can potentially cut production costs such as irrigation, weeding and fertilizers costs while increasing yield on a relatively small area.
Thesis (M.A. Agricultural Management (Plant Production)) -- University of Limpopo, 2023
Keywords: Organic medium; Species; Amaranth; Compositions; Organic farming; Species; Amaranth products